Development of Physics Learning Module Using Research Based Learning Model Integrated with Soil Pollution for MAN Students - Losita Dewi; Yeva Lenda Mahyastuti; Arya Ningsih (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine the practicality of the physics learning module using the Reseacrh Based Learning model integrated with soil pollution for Madrasah Aliyah Negeri (MAN) students. The type of research is Research & Development (R&D) research with the Ploomp model. The population of this study came from class XI students of MAN 2 Sungai Penuh. The research sample was XI science class of MAN 2 Full River. This research instrument is a test, validation sheet and practicality. Tests are used to determine the competence of knowledge, attitudes and skills of students. Data analysis is quantitative analysis. The results concluded that the validity value of the physics learning module using integrated Research Based Learning on soil pollution the practicality value from students was 84.19 % and the response from teachers was 87.5 %. This finding shows that the physics learning module using the Reseach Based Learning model integrated with soil pollution is very valid and practical to be applied in science learning.